2001
DOI: 10.1051/0004-6361:20000338
|View full text |Cite
|
Sign up to set email alerts
|

High resolution spectroscopy of symbiotic stars

Abstract: Abstract. We present new dynamical parameters of the AR Pav binary system. Our observations consist of a series of high resolution optical/NIR spectra from which we derive the radial velocity curve of the red giant as well as its rotation velocity. Assuming co-rotation, we determine the stellar radius (130 R ) of the red giant. Based on this we derive the red giant's luminosity and mass (2.0 M ) as well as the distance of the system (4.9 kpc). The binary mass function finally yields the companion's mass (0.75 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 20 publications
5
35
1
Order By: Relevance
“…AR Pav: during epochs 59−63 (1987-1995) of its historical light curve, Skopal et al (2000) estimated R e /A = 0.05 ± 0.02 (see Fig. 1 there), which for A = 419 R (Schild et al 2001) implies R d = 21±8 R . AX Per: recently, Skopal et al (2011) derived R d = 27 ± 2 R from the 2009 eclipse, which developed during the 2007−10 active phase.…”
Section: Column Density Of the Neutral Hydrogenmentioning
confidence: 95%
“…AR Pav: during epochs 59−63 (1987-1995) of its historical light curve, Skopal et al (2000) estimated R e /A = 0.05 ± 0.02 (see Fig. 1 there), which for A = 419 R (Schild et al 2001) implies R d = 21±8 R . AX Per: recently, Skopal et al (2011) derived R d = 27 ± 2 R from the 2009 eclipse, which developed during the 2007−10 active phase.…”
Section: Column Density Of the Neutral Hydrogenmentioning
confidence: 95%
“…With the parameters adopted above the orbital velocities of the two stellar components with respect to the center of mass are v rg = 4.6 km s −1 for the red giant and v hc = 13.8 km s Schild et al 2001) yields a mean radial velocity of 36.7 km s −1 with a scatter of σ = 1.1 km s −1 for 16 measurements taken between April 1992 and December 1997. Our FEROS spectra provide daily radial velocities for the red giant.…”
Section: Parameters For Mwc 560 Binary Systemmentioning
confidence: 99%
“…It was suggested that "symbiotic dust" carries as much information as symbiotic emission lines (Angeloni et al 2007c), and the unique CH Cyg mid-IR spectra recorded by the ISO satellite (Schild et al 1999) complicated furthermore the system overall picture. Multiple dust shells, mixed grain chemistry, equilibrium between grain formation and destruction processes in the turbulent nebulae (Angeloni et al 2007a) are worth investigating with the new era of mm-IR facilities, such as ALMA and Herschel.…”
Section: Observational Progressmentioning
confidence: 99%
“…Regarding the infrared range, it is worth reminding some results of 1997 ISO observations, unfortunately still no fully exploited. Schild et al (1999), who did a preliminary analysis of the spectra, found no strong emission lines but [OI]63 µm, and strong OH and weak H 2 O molecular emission on top of a rapidly decreasing continuum. This continuum can be fitted by a single dust shell model (T d ∼ 1000K, Fig.…”
Section: -1997 Transition Phase: the Contribution Of Radio Synchrmentioning
confidence: 99%